Peran Dukungan Orang Tua dan School Well-Being dalam Meningkatkan Motivasi Belajar Siswa - Vanny Dwi Hermawati; Bawinda Sri Lestari; Herlan Pratikto (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract This study aims to examine the relationship between parental support and school well-being with students' learning motivation. The subjects of this research were students of SMP Negeri 17 Surabaya, with a total population of 883 students. A sample of 125 students was selected using purposive sampling technique. The data were initially analyzed using multiple linear regression, which was later adjusted to the Spearman Rho method. The findings revealed that both parental support and school well-being simultaneously have a significant relationship with students' learning motivation. Furthermore, each independent variable also demonstrated a significant partial correlation with the dependent variable. The implications of this research highlight the essential role of emotional support and a positive school environment in fostering students' academic development. Keywords: Learning Motivation, Parental Support, School Well-Being Abstrak Kajian memiliki tujuan guna mencari tahu hubungan antara dukungan orang tua dan school well-being dengan motivasi belajar siswa. Subjek pada kajian ini adalah siswa SMP Negeri 17 Surabaya dengan jumlah populasi 883 siswa dan sampel sebanyak 125 siswa yang dipilih mengenakan teknik purposive sampling. Teknik analisis yang dikenakan yaitu regresi linear berganda, kemudian beralih menjadi Spearman Rho. Luaran kajian membuktikan bahwa dukungan orang tua dan school well-being secara simultan memiliki hubungan yang signifikan dengan motivasi belajar, dan secara parsial tiap-tiap variabel bebas juga menunjukkan hasil signifikan. Implikasi dari kajian ini menekankan pentingnya dukungan emosional dan lingkungan dalam perkembangan akademik siswa. Kata Kunci: Dukungan Orang Tua, Motivasi Belajar, School Well-Being